Temperature Dependent Piezoelectric Properties of Lead-Free (1-x)K0.6Na0.4NbO3–xBiFeO3 Ceramics - Khesro, Amir; Wang, Dawei; Hussain, Fayaz; Muhammad, Raz; Wang, Ge; Feteira, Antonio; Reaney, Ian M. (Frontiers in Materials, 2020)
(1-x)K0.4Na0.6NbO3–xBiFeO3 lead-free, piezoelectric ceramics were successfully prepared in single perovskite phase using the conventional solid-state synthesis. Relative permittivity (r) as a function of temperature indicated that small additions of BiFeO3 not only broadened and lowered the cubic to tetragonal transition (TC) but also shifted the tetragonal to orthorhombic phase transition (TO-T) towards room temperature. Ceramics with x = 1 mol. % showed optimum properties with small and large signal piezoelectric coefficient, d33 = 182 pC/N and d*33 = 250 pm/V, respectively, electromechanical coupling coefficient, kp = 50 % and TC = 355 °C. kp varied by ~ 5 % from RT to 90 °C, while d*33 showed a variation of 15 % from RT to 75 °C, indicating that piezoelectric properties were stable with temperature in the orthorhombic phase field. However, above the onset of TO-T, the properties monotonically degraded in the tetragonal phase field as TC was approached.